Analysis of Distance Learning Implementation from the Teacher's Perspective (Case Study: Sdit Al Iman Bintara) - Tissa Maharani (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
This study aims to analyze and explain how the implementation of distance learning during the COVID-19 pandemic by first graders teacher. How the learning process  was held, what information and communication technology was used, how was the preparation, what obstacles are faced by the respondents. The research method used a case study of descriptive qualitative approach with a phenomenological paradigm. The research subject is the first grade teacher of SDIT Al Iman Bintara. Data collection techniques using observation and questionnaires conducted online. Data analysis used descriptive statistics, with stages of data reduction, data presentation and conclusions. The result of the research is that the implementation of distance learning at SDIT Al Iman Bintara is running well according to the policies and technical implementations made by the school. The most widely used information and communication technologies during distance learning are Zoom, Edmodo and WhatsApp. The use of information and communication technology makes it easier for respondents in teaching activities, because previously respondents had attended special training from schools. Although 100% of respondents are used to using it every day, there are still obstacles that occur, such as internet signals that are not supported (disconnected/disappeared) or signal struggles with fellow teachers at school; internet packages for educators from the government that are not enough to use for one month when teaching from home; the material presented is less understandable by students, especially when there is a signal problem, which makes students no longer want to continue learning even though the signal is smooth again